Spectroscopic and X-ray Modeling of the Strong Lensing Galaxy Cluster MACS J0138.0-2155 - Abigail Flowers; Jackson H. O'Donnell; Tesla E. Jeltema; Vernon Wetzell; M. Grant Roberts (The Open Journal of Astrophysics)
We model the total mass and galactic substructure in the strong lensing galaxy cluster MACS J0138.0-2155 using a combination of Chandra X-ray data, Multi-Unit Spectroscopic Explorer (MUSE) spectroscopy, and Hubble Space Telescope imaging. MACS J0138.0-2155 lenses a source galaxy at $z=1.95$ which hosts two strongly lensed supernovae, Requiem and Encore. We find MACS J0138.0-2155 to have an X-ray temperature of $6.7±0.4$ keV and a velocity dispersion of cluster member galaxies of $718^{+132}_{-182}$ km s$^{-1}$. These lead to the mass estimates for the cluster of $M_{500} = 5.2^{+1.5}_{-1.2} × 10^{14} M_\odot$ from the X-ray results and $M_{200} ≈ 3.6^{+2.0}_{-2.7} × 10 ^{14} M_{\odot}$ from the velocity dispersion results. The round morphology of the X-ray emission indicates that this cluster is relaxed with an ellipticity within the lensing region of $e=0.12±0.03$. Using 18 of the brightest, non-blended, quiescent galaxies, we fit the cluster specific Faber-Jackson relation, including a set of 81 variations in the analysis choices to estimate the systematic uncertainties in our results. We find a slope of $α = 0.26 ± 0.06 (stat.) ± 0.03 (sys.)$ with an intrinsic scatter of $Δ σ = 31^{+8}_{-6} (stat.) ± 4 (sys.)$ km s$^{-1}$ at a reference velocity dispersion of $\sim 220$ km s$^{-1}$. We also report on significant galaxies along the line-of-sight potentially impacting the lens modeling, including a massive galaxy with stellar velocity dispersion of $236 ± 3$ km s$^{-1}$ which lies close in projection to the central cluster galaxy. This galaxy is part of a small group at a slightly higher redshift than the cluster.